Review on the Enhancement of Cyber Security Policies That Impacts the Employment System - Batumalai, Geevitha; Zolkipli, Mohamad Fadli (Journal of Applied Technology and Innovation, 2023)
In today’s environment, where almost everything has been digitalized, cybersecurity policies are crucial because of various security concerns and cyber-attacks. Security issues frequently affect many new developments. Security concerns prevent emerging technologies from being adopted and used, even if they have the potential to completely transform systems and people's lives. The constant improvement of cybersecurity policies has benefited both companies and employees. The research reviews enhancement of cybersecurity policies and how it affects the employment system, notwithstanding the sacred importance of cybersecurity policies in the digitalized world. The review shows that cybersecurity policies are essential for secure applications and a safer workplace. Although the idea of cyber risks conjures up images of outsiders, like hackers, attacking a company's systems or carrying out data theft, the most significant vulnerability in workplaces is typically the individuals who work there, which is the employees. This study concludes with a better grasp of how cybersecurity policies affect the employment system.